Contemporary principles of treatment ofchronicpainsyndromeinpatientswithbreastcancer - Z. V. Pavlova; K. P. Laktionov; M. Ye. Isakova; A. M. Pavlova; S. V. Pogodina (Опухоли женской репродуктивной системы)
Contemporary principles of treatment ofchronicpainsyndromeinpatientswithbreastcancer